KEWENANGAN IDEAL MAHKAMAH PELAYARAN DALAM MENYELESAIKAN KECELAKAAN KAPAL UNTUK MEWUJUDKAN KEADILAN - Sarwono, Sarif; Ismail; Iryani, Dewi (Collegium Studiosum Journal, 2025)
The Maritime Court (Mahkamah Pelayaran) is a judicial body under the Ministry of Transportation authorized to examine and adjudicate ship accidents, specifically regarding shipping safety aspects and the responsibility of masters or officers by imposing administrative sanctions. The regulations concerning the functions, authorities, and duties of the Maritime Court are governed by Law Number 66 of 2024 concerning the Third Amendment to Law Number 17 of 2008, specifically in Articles 251 to 253 of the Shipping Law. Article 251 of the Shipping Law outlines the functions of the Maritime Court; Article 252 details the authority to examine ship collisions occurring between commercial vessels, commercial and state vessels, as well as commercial and warships; and Article 253 defines the duties of the court, including investigating the causes of ship accidents, determining the presence of procedural errors or negligence by the master or officers, examining negligence by operators, ship owners, or officials that result in accidents, and recommending administrative sanctions to the Minister. The method used in this research is normative legal research conducted to obtain the necessary data related to the issues. The data used is secondary data consisting of primary, secondary, and tertiary legal materials, supported by primary data. Data analysis was performed using a qualitative juridical analysis method. The results of this research indicate that the current authority of the Maritime Court remains limited to administrative matters and has not yet addressed the need for more comprehensive justice for victims, ship owners, or aggrieved third parties, even though every ship accident involves not only technical navigation issues but also economic, environmental, and social impacts. Law Number 66 of 2024 has strengthened administrative sanctions but has not changed the position of the Maritime Court as a quasi-judicial institution. Therefore, a more integrative restructuring of authority is required so that the Maritime Court's decisions can be recognized as part of the judicial process and serve as considerations for judges in General Courts. This integrative process can be achieved by appointing the expert panels of the Maritime Court as ad hoc judges in General Courts. Thus, General Court decisions can create and strengthen the quality of rulings through precise and accurate maritime technical considerations given that the expert panels possess the background, experience, and specialized expertise in the shipping field while creating harmonization between Maritime Court decisions and General Court rulings to reduce contradictions and strengthen legal certainty.